ANALYSIS OF FAILED STUDENT MANAGEMENT SYSTEM AND ITS IMPACT ON EDUCATIONAL INEQUALITY IN 3T REGIONS - Aziza Turrohmah; Siti Aimah (As-Sulthan Journal of Education, 2024)
This study aims to analyze the failure of the student management system in Indonesia and its impact on educational inequality, especially in the 3T (Frontier, Remote, and Disadvantaged) areas. The main focus of the study is how weak data collection, distribution, and monitoring of students cause imbalances in access and quality of education in areas with limited infrastructure and resources. The method used is a qualitative approach with case studies in several junior high schools in East Seram Regency, Maluku Province. Data collection techniques were carried out through in-depth interviews with school principals, teachers, and school data managers, as well as document analysis and field observations. The results of the study indicate that the student management system that is not running optimally such as errors in student data, delays in integration with the central system, and lack of HR training contributes to the uneven allocation of educational assistance and limited policy interventions. This study makes an important contribution in strengthening the urgency of an inclusive and adaptive education data management system to the geographical and social context of the 3T areas, in order to create justice and equity in education throughout Indonesia.